2002
DOI: 10.1038/415655a
|View full text |Cite
|
Sign up to set email alerts
|

An exonucleolytic activity of human apurinic/apyrimidinic endonuclease on 3′ mispaired DNA

Abstract: Human apurinic/apyrimidinic endonuclease (APE1) is an essential enzyme in DNA base excision repair that cuts the DNA backbone immediately adjacent to the 5' side of abasic sites to facilitate repair synthesis by DNA polymerase beta (ref. 1). Mice lacking the murine homologue of APE1 die at an early embryonic stage. Here we report that APE1 has a DNA exonuclease activity on mismatched deoxyribonucleotides at the 3' termini of nicked or gapped DNA molecules. The efficiency of this activity is inversely proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
197
2
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(204 citation statements)
references
References 23 publications
4
197
2
1
Order By: Relevance
“…32 In addition to AP endonuclease activity, APE1 also possesses 3 0 -phosphodiesterase, 3 0 -phosphatase and 3 0 -5 0 -exonuclease functions specific for the 3 0 termini of internal nicks and gaps in DNA. [33][34][35] The present study found that APE1 was strongly expressed in LOVO cells and the expression of APE1 was increased by irradiation, probably representing an early event in the cell response to irradiation because of its role in DNA BER, and promoting radioresistance. Ad5/ F35-APE1 siRNA inhibited APE1 expression and AP endonuclease activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 87%
“…32 In addition to AP endonuclease activity, APE1 also possesses 3 0 -phosphodiesterase, 3 0 -phosphatase and 3 0 -5 0 -exonuclease functions specific for the 3 0 termini of internal nicks and gaps in DNA. [33][34][35] The present study found that APE1 was strongly expressed in LOVO cells and the expression of APE1 was increased by irradiation, probably representing an early event in the cell response to irradiation because of its role in DNA BER, and promoting radioresistance. Ad5/ F35-APE1 siRNA inhibited APE1 expression and AP endonuclease activity in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 87%
“…76 APE1 has been suggested to act as a proofreading enzyme for mistakes made by Pol β during BER gap filling synthesis. 77 Several APE1 variants in the general population have functional phenotypes. The APE 1 gene maps to chromosome 14q11.2-q12.…”
Section: Ape1 Alterations and Expression Levels May Be Linked To Cancmentioning
confidence: 99%
“…APEs from both families are also capable of acting as 3′ f 5′ exonucleases at nicks (16,17); because this activity is most efficient for nicks containing a 3′ mismatched base pair, it is speculated to enhance the fidelity of DNA repair by providing, in trans, the proofreading activity that is typically absent in repair polymerases (16).…”
mentioning
confidence: 99%
“…APEs from both families are also capable of acting as 3′ f 5′ exonucleases at nicks (16,17); because this activity is most efficient for nicks containing a 3′ mismatched base pair, it is speculated to enhance the fidelity of DNA repair by providing, in trans, the proofreading activity that is typically absent in repair polymerases (16). Most recently, APEs from both protein families have been shown to catalyze nucleotide incision repair (NIR) in which, bypassing the step of base removal by a DNA glycosylase, the APE directly incises the sugar-phosphate backbone 5′ to a nucleotide containing a damaged base 3 to generate a single-nucleotide gap flanked by a 3′-hydroxyl and a 5′-"dangling nucleotide"-which can subsequently be removed by a flap endonuclease 1 (FEN1)-like activity (18)(19)(20)(21).…”
mentioning
confidence: 99%